(untitled) (Innovaciones Educativas, 2022)
The social confinement derived from the COVID-19 pandemic caused worldwide problems in education during the 2020-2021 school year. In the face of this new normality, dilemmas were found in higher education institutions, to promote equity in access to higher education. The purpose of this article is to describe the educational public policy actions implemented at Universidad Pedagógica Veracruzana (UPV) -as a case study- to address equity in access to initial teacher training for the 2020-2021 school year. Based on a quantitative methodology and using various sources of evidence, a database of 2,260 records was analyzed, in addition to a retrospective documentary research. The most relevant results of this study focus on two elements: the pre-decisional analysis of an educational public policy implemented to address the promotion of equity in university access; in other words, it shows the public problem, the possible options to address it, the decision making process by means of an academic strategy and its application; it also describes the applicants and the results of their achievements in the process. In conclusion, a successful case is identified promoting the achievement of university applicants by motivating the use of Information and Communication Technologies with relevance from the academic and social perspective, which allows seeking other routes for educational research, with a prospective vision in the equity of higher education.